APR-246 enhances the anticancer effect of doxorubicin against p53-mutant AsPC-1 pancreatic cancer cells - Ali Haider Alhammer; Shaymaa Ismael Al-juboori; Shahad Ali Mudhafar (مجلة بغداد للعلوم, 2024)
Pancreatic cancer (PC) is a disease with a high mortality rate, and the early diagnosis of PC is still challenging. The 5-year relative survival rate remains below 8%, and therapeutic strategies are ineffective at increasing patient survival rates. In PC cells, resistance to treatment has been associated with genetic changes that initiate aberrant developmental signaling pathways; therefore, new strategies for treating PC are warranted. Here, we sought to explore the small molecule p53 reactivator, APR-246, either as a mono-drug or combined with doxorubicin (Doxo) in the p53 mutant (p53-mut) AsPC-1 PC cell line. Cytotoxicity of APR-246 and Doxo was studied alone or in combination with the AsPC-1 cell line with MTT assay. CalcuSyn software was used to calculate the combination index (CI), which was based on the Chou and Talalay technique. Apoptosis was assessed after staining with Acridine orange/ethidium bromide (AO/EB). Morphological alterations were examined under a 200x magnification by an inverted microscope. Gene expression was quantified using quantitative reverse transcription PCR assay (RT-qPCR). APR-246 alone exhibited modest anti-proliferative effects, while Doxo combined with APR-246 showed synergistic effects associated with morphological change; no more enhanced apoptosis was observed, as supported by NOXA gene levels. In conclusion, APR-246, whether monotherapy or combined with Doxo, was hindering the proliferation of p53-mut AsPC-1 PC cells, and further in vitro and in vivo research is warranted.